One-step Solvothermal Synthesis of Two-dimensional Ultrathin Na3[Ti2P2O10F] Nanosheets for Lithium/Sodium Storage. (20th August 2017) - Hu, Linyu; Hou, Junke; Yi, Fenglian; Chen, Yuming; Niu, Yubin; Han, Jin; Zhang, Yan; Lu, Zhisong; Xu, Maowen
Highlights: Ultrathin Na3 [Ti2 P2 O10 F] nanosheets with the thickness of 1 ∼ 2 nm are effectively synthesized by a single-step solvothermal method. The as-prepared 2D ultrathin Na3 [Ti2 P2 O10 F] nanosheets exhibit good electrochemical properties for Li-ion and Na-ion batteries. This work would provide new avenues for the rational engineering of 2D nanosheet structure for many applications. Abstract: Na3 [Ti2 P2 O10 F], a novel oxyfluorinated titanium phosphate, is a promising anode material for lithium/sodium storage because of its open framework structure and marvelous two-dimensional (2D) tunnel. However, 2D nanostructured Na3 [Ti2 P2 O10 F] has been rarely prepared in view of the limitations of synthetic approaches. Here we report a one-step, low-cost solvothermal method for the synthesis of 2D ultrathin Na3 [Ti2 P2 O10 F] nanosheets with the thickness of 1 ∼ 2 nm. Benefiting from the desired crystal and structural characteristics, these as-prepared ultrathin 2D Na3 [Ti2 P2 O10 F] nanosheets exhibit good electrochemical performance for Li-ion and Na-ion batteries.